Teaching with emotion : a postmodern enactment - Zembylas, Michalinos (Emerald Publishing Limited : Information Age Pub., 2005)
The purpose of this book is to provide new theoretical, methodological and empirical directions in research on teacher emotion. An attempt is made to encourage a missing conversation in the area of emotions in teaching, by invoking a discussion of ideas that explore how discursive, political and cultural aspects define the experience of teacher emotion. I begin to build an analysis upon which the role of emotion, emotional rules and emotional labor in curriculum and teaching might be investigated. This book includes both conceptual chapters and chapters based on empirical work--and, in particular, a three-year ethnographic study with an early childhood teacher in the context of science teaching--that together illustrate new approaches and perspectives in researching and theorizing about emotion in teaching Essentially, then, there are two overlapping aims in this book. First, to critically examine some of the contemporary ways in which emotions have been conceptualized and understood in teaching; and second, to explore the role of emotion in teaching through different methodologies and theorizations.
Keywords: Teachers -- Psychology.; Emotions.; Postmodernism and education.; Education -- Educational Psychology.; Teaching staff.; Educational psychology.; elektronické knihy; electronic books